2004
DOI: 10.1007/s00167-003-0467-3
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral relationships and cartilage breakdown

Abstract: We evaluated the association between patellofemoral relationships and cartilage lesions in patients (age range 15-49) with anterior knee pain without patellar dislocation (n = 24) and in patients with isolated meniscal rupture without a high energy trauma (n = 21). The position of the patella was assessed from knee radiographs, and cartilage lesion was graded and mapped at arthroscopy. In subjects with lateral patellar cartilage lesion the patella tilted laterally (p < 0.01) and was clearly laterally displaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
3
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
(17 reference statements)
2
17
3
3
Order By: Relevance
“…7,12,38,44 These studies state that the lateral patellar facet is mainly involved with chondromalacia patellae and with patellofemoral compression syndrome, while either the lateral or medial facets can be damaged with patellar malalignment. This literature on patellofemoral dysfunction and pain describes increased lateral contact and patellofemoral joint pressure, 6,7,21,22,42,44,48 and suggests an increase in lateral patellar and lateral femoral articular wear. This literature also indicates that the medial facet shows more degeneration with aging than the lateral facet.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12,38,44 These studies state that the lateral patellar facet is mainly involved with chondromalacia patellae and with patellofemoral compression syndrome, while either the lateral or medial facets can be damaged with patellar malalignment. This literature on patellofemoral dysfunction and pain describes increased lateral contact and patellofemoral joint pressure, 6,7,21,22,42,44,48 and suggests an increase in lateral patellar and lateral femoral articular wear. This literature also indicates that the medial facet shows more degeneration with aging than the lateral facet.…”
Section: Specimensmentioning
confidence: 99%
“…There were 13 males and 13 feor damage to the medial patellar facet, 3,12,15,26,29,38,44,49,50 the lateral patellar facet, 3,6,7,12,15,21,26,29,35,44,48,49,52 the central patella, 12,21,38,44 the medial femoral condyle, 7,12,44 and the lateral femoral condyle. 7,12,38,44 These studies state that the lateral patellar facet is mainly involved with chondromalacia patellae and with patellofemoral compression syndrome, while either the lateral or medial facets can be damaged with patellar malalignment.…”
Section: Specimensmentioning
confidence: 99%
“…Additionally, the Q -angle as measured as the tibial tubercle-trochlear groove distance (TT-TG) has been found to be greater in those with PFOA [2]. To date, there have been few reports comparing PFJD to radiographic indices of patellofemoral alignment [5, 11, 14]. One study did find that individuals with lateral-sided PFJD had greater lateral patella tilt and displacement and no difference in patella height [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies assessed the PF dysfunction but not specifically relate the observed retropatellar cartilage changes to the kneeling ability. Certain studies described the damage in the medial facet [14,[19][20][21][22][23]; the lateral facet [14,19,20,[22][23][24][25][26][27][28]; the central patella [22,23,25]; the medial femoral condyle [23,24] and the lateral femoral condyle [22][23][24]. These studies reported that the lateral and medial facets could be damaged with malalignment of the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover; the lateral patellar facet is mainly involved with chondromalacia patellae and with patellofemoral compression syndrome. Studies on patellofemoral dysfunction and pain describe increased lateral contact and patellofemoral joint pressure [13,17,18,[23][24][25] and suggests an increase in lateral patellar and lateral femoral articular wear. These studies also indicate that the medial facet shows more damage with aging than the lateral facet [20,22] which is different than the observed RPC damages in this study; the lateral facets and medial facets almost equally affected.…”
Section: Discussionmentioning
confidence: 99%